2019 13th International Conference on Research Challenges in Information Science (RCIS) 2019
DOI: 10.1109/rcis.2019.8876959
|View full text |Cite
|
Sign up to set email alerts
|

Procrastination on Social Networking Sites: Combating by Design

Abstract: Procrastination refers to a voluntary postponement that prevents people from performing their tasks and can hurt productivity and wellbeing. Procrastination might occur due to a lack of motivation to perform tasks or due to the low self-control that people might have over their time and task management. Social Networking Sites (hereafter SNS) are designed to enable their users to engage in online interaction for different purposes such as increasing popularity or exploring information. SNS embed influence and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

5
1

Authors

Journals

citations
Cited by 6 publications
(22 citation statements)
references
References 39 publications
1
21
0
Order By: Relevance
“…For example, FoMO on instant messaging has a different nature and patterns on online forums. Using such a democratic technique can bring in-depth insight into the method design, and thus allowing a better understanding of the target population and a more effective design of the countermeasures [ 68 , 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, FoMO on instant messaging has a different nature and patterns on online forums. Using such a democratic technique can bring in-depth insight into the method design, and thus allowing a better understanding of the target population and a more effective design of the countermeasures [ 68 , 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…The findings are meant to inform the literature on how SNS facilitate procrastination as a first step to designing persuasive techniques to counterbalance that side-effect. Hence, we used our findings in [10] as a baseline for devising countermeasures to combat procrastination on SNS.…”
Section: Introductionmentioning
confidence: 99%
“…This may be interconnected with digital addiction, where the desire to achieve mood modification leads individuals to use social media as a way to avoid stressful or demanding tasks [ 8 ]. Procrastination means a delay of another task and our previous research in [ 8 , 12 , 13 ] showed that users wish to see motivational elements in that task that then add a degree of satisfaction that they get from social media, for example, being rewarded, task completion and getting social support while doing it.…”
Section: Introductionmentioning
confidence: 99%
“…While social media has brought many benefits, such usage styles can be seen as problematic, resulting in reduced academic performance, lack of real-world social skills, neglecting meals and physical activities. Our previous work has also demonstrated that the design of SNS features plays a significant role in facilitating procrastination [ 8 , 12 , 13 ]. This indicates that a method to combat procrastination on SNS needs to build resilience to these SNS triggers and utilise additional features to combat them.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation